Health risks and developmental transitions during adolescence (Cambridge University Press, 1997)
This book focuses on the different developmental transitions during adolescence and young adulthood and relates them to risks and benefits for young people's health and well-being. This book advocates the broadening of the concept of health promotion to include assistance with negotiating the several changes that occur as individuals move into and out of adolescence. Chapters from many of the most prominent researchers in the adolescent field from several countries are included in this edited volume.